Benzoylquinazolinone derivatives as new potential antidiabetic agents: α‐Glucosidase inhibition, kinetic, and docking studies. Issue 5 (24th November 2019) - Mohammadi‐Khanaposhtani, Maryam; Yahyavi, Hoda; Imanparast, Somaye; Harandi, Fereshte Nazemi; Faramarzi, Mohammad Ali; Foroumadi, Alireza; Larijani, Bagher; Biglar, Mahmood; Mahdavi, Mohammad
Abstract: Benzoylquinazolinone derivatives 3a–n were synthesized via a simple one‐step reaction, and evaluated for in vitro α‐glucosidase inhibitory activity. Compounds 3d, 3f–g, 3i, and 3m–n showed more inhibitory activity than standard drug acarbose (IC50 = 750.0 ± 1.5 μM), and among them, compound 3d displayed the highest α‐glucosidase inhibitory activity (IC50 = 261.6 ± 0.1 μM). The kinetic analysis of the compound 3d revealed that this compound inhibited α‐glucosidase in a competitive manner ( K i = 255 μM). The docking studies were applied to predict binding modes of the synthesized compounds in active site of α‐glucosidase. Abstract : Benzoylquinazolinone derivatives 3a–n were synthesized via a simple one‐step reaction, and evaluated for in vitro α‐glucosidase inhibitory activity. Compounds 3d, 3f–g, 3i, and 3m–n showed more inhibitory activity than standard drug acarbose (IC50 = 750.0 ± 1.5 μM), and among them, compound 3d displayed the highest α‐glucosidase inhibitory activity (IC50 = 261.6 ± 0.1 μM). The kinetic analysis of the compound 3d revealed that this compound inhibited α‐glucosidase in a competitive manner ( K i = 255 μM). The docking studies were applied to predict binding mode of the synthesized compounds in active site of α‐glucosidase.